Effects of Stroke Volume Maximization Before One-Lung Ventilation on Video-Assisted Thoracic Surgery: A Randomized Controlled Trial - Man-Ling Wang; Po-Ni Hsiao; Hsao-Hsun Hsu; Jin-Shing Chen; Ya-Jung Cheng (Diagnostics)
Background/Objectives: The use of goal-directed fluid therapy (GDFT) guided by stroke volume (SV) variation during thoracic surgery, particularly with one-lung ventilation (OLV) and protective ventilation strategies, is not well established. This study aimed to determine whether maximizing stroke volume (SV) before initiating one-lung ventilation (OLV) reduces the incidence of intraoperative hypotension requiring vasoactive agents during video-assisted thoracoscopic surgery (VATS). Methods: Sixty patients undergoing VATS were randomly assigned to an SVM group (n = 30) or a control group (n = 30). The SVM group received 6% hydroxyethyl starch before OLV to achieve and maintain an SV increase of less than 10%. The control group received no active fluid therapy before OLV positioning. Both groups received Ringer’s lactate solution intraoperatively based on baseline (control) or maximized (SVM) SV goals. The primary outcome was the use of vasoactive agents for hypotension. Results: Patients in the SVM group received significantly less Ringer’s lactate solution than controls (4.2 ± 2.4 vs. 6.1 ± 2.8 mL/kg/h, p = 0.005). While fewer patients in the SVM group required vasoactive agents (20% vs. 40%), the difference was not statistically significant (p = 0.091). IL-6 levels were significantly lower during OLV in the SVM group. Conclusions: Pre-OLV SVM was associated with reduced intraoperative crystalloid administration and attenuation of inflammatory response, with a non-significant trend toward lower vasopressor use. These findings suggest a potential benefit of SVM in thoracic surgery, though larger multicenter trials are needed to confirm clinical efficacy.